A Semantic Analysis on Maroon 5 Songs - Wiwin Pasisingi; Ana Mariana; Dahlia Husain (Journal of English Language Teaching, Linguistics, and Literature Studies, 2022)
The research aims to find out lexical and contextual meaning in the lyrics of Maroon 5 songs. This research chose five songs from Maroon 5; titled Maps, Leaving California, In Your Pocket, New Love, and Sugar. The research method used descriptive qualitative. The focus of this research is describing the context found lexical and contextual meaning theory by Mansoer Pateda to conduct this research. The step to obtain the data is collecting source of the data from Maroon 5 songs taken from the internet. After that, the writers select, read and listen the songs which contain lexical and contextual meaning the content of the songs. As a result of this research, it found 34 dates with lexical and contextual meanings. The result of this research is a complex romantic love story, or the bitter sweetness of a relationship of happiness, betrayal, struggle, and even loss.Keywords: semantic, lexical meaning, contextual meaning, songs, Maroon 5